HUBUNGAN ANTARA KONDISI FISIK RUMAH DAN KEBIASAAN MEROKOK DALAM RUMAH DENGAN ISPA PADA BALITA - Puti Widya Gravinta; Didi Yunaspi; Afif D Alba (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: ARI disease in toddlers is important to note because ARI is an acute disease that can cause death in toddlers in various developing countries including Indonesia. The purpose of this study was to determine the relationship between the physical condition of the house and smoking habits in the house with the incidence of ARI in toddlers in the Working Area of Tanjung Uncang Health Center, Batam City in 2024. This study is a quantitative study using a correlative design with a cross sectional approach to 95 parents who have toddlers. The implementation time began on July 27, 2024 until August 30, 2024. Sampling using purposive sampling technique. Measuring instruments used medical record observations, questionnaires and observation sheets. Data analysis used is chi square test. The physical condition of the house did not meet the requirements, which amounted to 53 parents (55.8%), smoking habits in the house, which amounted to 71 parents (74.7%), and the incidence of ARI in toddlers, which amounted to 53 parents (55.8%). The results of the chi square test of the variable physical condition of the house obtained a p value of 0.000 0.05 which means H0 is rejected and Ha is accepted, so there is a significant relationship between the physical condition of the house and the incidence of URI. In the variable smoking habits in the house obtained a p value of 0.000 0.05 which means H0 is rejected and Hɑ is accepted, so there is a significant relationship between smoking habits in the house with the incidence of ARI. Conclusion on.Keywords: House Condition, Smoking Habits, ISPA.